The Role of the Police in Handling Traffic Violations Based on Justice Values (Research Study at the Natuna Police Resort) - Pasmah, Sadeva Abdie Wahyu; Winjaya Laksana, Indra (UNISSULA Semarang, 2025)
Abstract. Fair and proportional traffic law enforcement is an important part of creating road safety and order. However, in practice, overcoming traffic violations often not only face technical challenges, but also touch on aspects of legal and social justice. This research aims to analyze the role of the traffic police in tackling traffic violations based on the value of justice, with a focus on implementation in the jurisdiction of the Natuna Resort Police. This research uses normative juridical and empirical juridical approaches, by examining applicable laws and regulations, such as Law No. 2 of 2002 concerning Police and Law No. 22 of 2009 concerning Road Traffic and Transportation, as well as collecting primary data through interviews and field observations. The theoretical framework used includes Lawrence M. Friedman's legal system theory, Barda Nawawi Arief's crime prevention theory, and John Rawls and Aristotle's theory of justice. The results show that the role of the police in tackling traffic violations in Natuna has been running with a combination of preventive and repressive strategies, but its effectiveness is still constrained by limited human resources, infrastructure, the unavailability of the ETLE system, and low public legal awareness. In addition, there are still inconsistencies in law enforcement that have an impact on the perception of injustice among the community. This study recommends that the police increase institutional capacity, expand traffic law education programs, and strengthen cross-sector synergies with the support of regional regulations. Law enforcement that prioritizes the principles of justice, transparency, and community participation is key in realizing a safe and orderly traffic system.